Efektivitas Perda Minuman Keras - Harahap, Ardiansyah; Dalimunthe, Dermina (Jurnal El-Thawalib, 2021)
The background of this research problem is the effectiveness of the implementation of the Regional Regulation Number 7 of 2005. This of course has an impact on the lack of level of public understanding of local regulations regarding the prohibition of the sale and distribution of liquor, it causes more and more people to sell and distribute liquor. The formulation of the problem of this research is how the effectiveness of implementing the regional regulations of the City of Padangsidimpuan Number 7 of 2005 concerning the prohibition of the sale and distribution of liquor in the VII Environment of Batunadua Jae Village, Padangsidimpuan City and the factors that become obstacles in the implementation of the Padangsidimpuan City area Number 7 of 2005 concerning the prohibition of sales and distribution. liquor in the VII Ward of Batunadua Jae Urban Village, Padangsidimpuan City. This type of research used by researchers is field research (field research) which took place in the KelurahanBatunaduajae and the Office of the SATPOL PP Padangsidimpuan City. So to find out the results or the correctness of the problems in this study, researchers used data collection instruments by means of interviews and documentation. Meanwhile, data management is done by identification, category, analysis, and conclusions. The results obtained from this study indicate that the implementation of regional regulation number 7 of 2005 concerning the prohibition of the sale and distribution of liquor has not been effective, because there are still many fields that sell and distribute liquor in the VII Ward of Batunadua Jae Village, Padangsidimpuan City.